2016
DOI: 10.1161/atvbaha.116.307285
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Calpain Deficiency Reduces Angiotensin II–Induced Inflammation and Atherosclerosis But Not Abdominal Aortic Aneurysms in Mice

Abstract: Objective Angiotensin II (AngII)-infusion profoundly increases activity of calpains, calcium-dependent neutral cysteine proteases, in mice. Pharmacological inhibition of calpains attenuates AngII-induced aortic medial macrophage accumulation, atherosclerosis, and abdominal aortic aneurysm in mice. However, the precise functional contribution of leukocyte-derived calpains in AngII-induced vascular pathologies has not been determined. The purpose of this study was to determine whether calpains expressed in bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 44 publications
(59 reference statements)
6
41
0
Order By: Relevance
“…Accumulative studies reported that the increase in production of endothelial NO protected animals against atherosclerosis (De Caterina et al 1995;Momi et al 2012;Zeiher et al 1995). Regarding the roles of calpain-1 and calpain-2 in the formation of atherosclerosis, both calpain-1 and calpain-2 are reportedly expressed in macrophages in angiotensin II-infused athero-prone aorta, and are associated with their inflammatory responses (Howatt et al 2016). In addition, calpain-2 appears to be upregulated in vascular endothelium during atherogenesis, and is contributed to endothelial barrier dysfunction (Miyazaki et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulative studies reported that the increase in production of endothelial NO protected animals against atherosclerosis (De Caterina et al 1995;Momi et al 2012;Zeiher et al 1995). Regarding the roles of calpain-1 and calpain-2 in the formation of atherosclerosis, both calpain-1 and calpain-2 are reportedly expressed in macrophages in angiotensin II-infused athero-prone aorta, and are associated with their inflammatory responses (Howatt et al 2016). In addition, calpain-2 appears to be upregulated in vascular endothelium during atherogenesis, and is contributed to endothelial barrier dysfunction (Miyazaki et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Subramanian et al also showed that atherosclerotic lesion progression in angiotensin II-infused Ldlr -/-mice is impaired by the calpain inhibitor BDA-410 [50]. Transgenic overexpression of calpastatin appears to significantly attenuate angiotensin IIor hypercholesterolemia-induced atherosclerotic development in Ldlr -/-mice, while abdominal aneurysmal formation was unchanged [51]. In mice, either myeloid calpain-1 or leukocyte calpain-2 are involved in angiotensin II-induced atherosclerosis [51].…”
Section: Calpain and Atherogenesismentioning
confidence: 99%
“…Transgenic overexpression of calpastatin appears to significantly attenuate angiotensin IIor hypercholesterolemia-induced atherosclerotic development in Ldlr -/-mice, while abdominal aneurysmal formation was unchanged [51]. In mice, either myeloid calpain-1 or leukocyte calpain-2 are involved in angiotensin II-induced atherosclerosis [51]. Thus, it is likely that conventional calpains are involved in pro-atherogenic regulation of EC and leukocytes.…”
Section: Calpain and Atherogenesismentioning
confidence: 99%
“…93 Furthermore, compared with nonmanipulated Ldlr-null mice, atherosclerosis was increased with concurrent deficiency of the sheddase, a disintegrin and metalloproteinase 17, 94 96 and also decreased (together with decreased aortic aneurysm development) in mice with leukocyte-specific calpain 2 deficiency. 97 Newer genetically manipulated mouse models have also contributed valuable pieces of information to the overall puzzle of atherosclerosis. For instance, high expression levels of telomerase reverse transcriptase in mice induce atherosclerosis-like smooth muscle cell morphology, whereas deletion of TERT decreases neointima formation through epigenetic regulation of proliferative gene expression.…”
Section: Defining Atherosclerosis In Animal and Cellular Modelsmentioning
confidence: 99%